Pengaruh Latihan Fisik Ibu Hamil Terhadap Penurunan Tingkat Nyeri Punggung Ibu Hamil Trimester III - Sari, Puput Kurnia; Aulia; Niken Wahyu Hidayati; Sitti Sarti (Universitas Muhammadiyah Gresik, 2025)
Background: The pregnancy process itself involves various physiological changes, including physical changes, changes in the digestive system, respiratory system, urinary tract system, musculoskeletal system, and circulatory system. Objective : The purpose of this study was to determine the effect of physical exercise on the level of back pain in pregnant women in their third trimester. Method: This study is a quantitative study using a pre-experimental design, which involves administering an intervention to one or more groups to assess its effects. The study was conducted at the Pabelan Health Center. The population in this study was pregnant women who had entered their third trimester of pregnancy. The sample in this study was obtained using purposive sampling techniques, determined based on criteria set by the researcher during data collection throughout the study. Results: Based on the results of the Wilcoxon Signed Ranks Test, the p-value was 0.000. Since 0.000 < 0.05, it was decided to reject H0 and accept H1. Therefore, it can be concluded that there is a significant effect between physical activity and back pain in pregnant women in the third trimester. Conclusion: There is an effect of physical exercise on back pain in pregnant women in the third trimester.